Study on the permanent deformation of asphalt mixtures based on the modified Burgers model - Yang, Junren; Xie, Jun; Tang, Xu; Zhang, Haijun (Frontiers in Built Environment, 2024)
Based on the confined test results and the viscoelastic constitutive model of asphalt mixtures, a three-dimensional finite element model of the asphalt pavement was established to study the effect of different working conditions on the asphalt pavement. With the actual pavement structure response, a comparative analysis was conducted to assess the stress and strain experienced by the asphalt pavement under various working conditions. The results show that the asphalt pavement structure model can reflect the effect of different working conditions on the asphalt pavement; the transverse stress and strain of the asphalt pavement are most significantly affected by the working condition during cornering,and the position of the maximum value is concentrated on the outer edge line of the wheel and a distance away from it; however, the longitudinal tensile stress and strain of the asphalt pavement are most significantly impacted by the working conditions of driving and braking, and the position of the maximum value is mainly distributed in the center line of the single wheel. The research results can provide a reference for the design of asphalt pavement structure.